Drying method of polyester plain weave fabric base coating cloth with Chinese art paper wetting effect
By heating and dehydrating the polyester and controlling the temperature during the drying process, the problem of citric acid decomposition is solved, the bonding force between the polyester and the slurry is enhanced, and the good hygroscopicity of the coating cloth is achieved, similar to the wetting effect of rice paper.
Patent Information
- Application Number
- CN202510044174.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-11
- Publication Date
- 2025-02-28
AI Technical Summary
During the drying process, citric acid is easily decomposed by temperature, resulting in a decrease in the bonding force between the polyester and the slurry and affecting the hygroscopicity of the coating cloth.
By heating and dehydrating the polyester and using hot air at controlled temperature during the drying process, the citric acid is not decomposed, causing the mixed slurry to penetrate along the pores of the polyester, and the reaction is completed under low temperature conditions.
It effectively avoids the decomposition of citric acid, enhances the bonding force between polyester and slurry, and makes the molded coating cloth have good hygroscopicity, similar to the wetting effect of rice paper.
Smart Images

Figure CN119531141A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of canvas drying, in particular to a drying method for a polyester plain weave fabric-based coated cloth having a rice paper wetting effect. Background Art
[0002] Xuan paper has good ink absorption, strong durability and aging resistance, and is not easy to change color. Xuan paper has the characteristics of toughness and moisture, glossy but not slippery, white and dense, pure texture, no damage when rubbed and folded, strong ink absorption, and unique penetration and lubrication properties. Therefore, Xuan paper is the best choice for traditional Chinese ink painting.
[0003] However, the production process of traditional Xuan paper is relatively long, generally including raw material processing, pulping, scooping, drying and other processes. The raw material processing process mainly uses the bark of the Chinese cedarwood tree and paddy straw. The bark of the Chinese cedarwood tree needs to be steamed, soaked, peeled, and aired. The peeled bark strips need to be debarked, pulped, and processed to ensure the purity and uniformity of the fibers. Therefore, high-quality Xuan paper requires the consumption of forests, and large-scale Xuan paper production comes at the expense of greening.
[0004] The pulping process is to put the processed leather and straw into the pounding room, and after repeated beating and chopping, form irregular triangular fibers; the paper scooping process is to pour the processed pulp into the water tank, use paper curtains to scoop out the pulp to form the initial form of rice paper. This step requires extremely high skills to ensure the uniformity and quality of the paper; the paper drying process is to place the scooped wet paper on a special paper drying machine to dry. This process requires control of temperature and humidity to ensure the quality and stability of the paper.
[0005] Based on the above technical conditions, it can be seen that traditional Xuan paper not only has high requirements for process technology, but also has high requirements for the environment, especially the paper drying process, which not only has requirements for weather and seasons, but also has high requirements for lighting conditions, etc. The above factors have actually seriously restricted the output of Xuan paper.
[0006] So if a canvas with a rice paper effect is designed as a substitute for traditional rice paper, it will certainly be able to overcome the many defects of traditional rice paper. To this end, the applicant applied for a rice paper-like coating and rice paper-like, preparation method and application thereof (CN117738024A) on December 4, 2023. During the production process, it was found that there was still room for improvement in the bonding degree between polyester and slurry. When trying to use citric acid as an intermediate medium, it was found that citric acid was easily affected by temperature during the drying process, resulting in a decrease in the bonding effect between polyester and slurry. Summary of the invention
[0007] The technical problem to be solved by the embodiments of the present invention is to provide a drying method for a polyester plain weave fabric-based coated cloth having a rice paper wetting effect, thereby solving the problem of manufacturing a coated cloth having a rice paper wetting effect by using polyester plain weave fabric as a base material.
[0008] In order to solve the above technical problems, the present invention provides a drying method for a polyester plain weave fabric-based coated cloth having a rice paper wetting effect, comprising: The first step is to heat and dehydrate the polyester, and then cool it down to between 30-40℃; The second step is to immerse the polyester in a 3-5wt% citric acid solution, and then blow hot air with a temperature not exceeding 60°C from bottom to top, so that the citric acid solution moves along the pores of the polyester to the upper surface to be concentrated in the pores and the upper surface of the polyester, and evaporate part of the water therein while keeping the citric acid from being decomposed; Step 3: Scrape the polyester upper surface with a mixed slurry whose main components are oxidized starch and carboxylated nanocellulose, and the hydroxyl functional group content of the oxidized starch in the mixed slurry is 1.05-1.1 times the carboxyl functional group content of the carboxylated nanocellulose; Step 4: Pressure drying the coated surface: Use hot air at 60-75℃ to blow downward from the upper surface of the polyester evenly, so as to make the mixed slurry penetrate downward along the pores of the polyester, and make the surplus hydroxyl groups of the oxidized starch in the mixed slurry contact and react with the citric acid on the upper surface of the polyester and in the gaps; Step 5: After the citric acid and oxidized starch have fully reacted, hot air at 78-90°C is blown from bottom to top on the lower surface of the polyester to evaporate the residual moisture and decompose the unreacted citric acid hydrate to obtain anhydrate, and ensure that the anhydrate of citric acid will not continue to decompose into carbon dioxide and water.
[0009] The carboxylated nanocellulose has a diameter of 10-20 nm and a length of 0.5-1 μm, so the aspect ratio is between 25-100.
[0010] The thickness of the polyester is 0.5 mm, and the fabric density is 300-400 strands / 10 cm.
[0011] Oxidized starch and water were mixed, heated at 95°C, and mechanically stirred at 230 rpm for 45 min. Then, the mixture was heated to 60°C for 15 min. At room temperature, the gelatinized oxidized starch solution and the cellulose nanofiber dispersion were mixed in a mass ratio of 2:8 and mixed evenly by magnetic stirring.
[0012] The scraping thickness d of the mixed slurry is 0.1-0.25 mm.
[0013] In the second step, the upper surface of the polyester is the starch-coated side and the lower surface is the non-starch-coated side.
[0014] In the third step, the mixing step of the mixed slurry of oxidized starch and carboxylated nanocellulose includes: Oxidized starch is made into gelatinized starch by adding water; preparing a carboxylated nanocellulose dispersion; The gelatinized starch and the carboxylated nanocellulose dispersion are mixed and stirred evenly.
[0015] In the third step, the mixed slurry also includes thickener, preservative, leveling agent, dispersant, defoaming agent, etc.
[0016] In the fourth step, the drying time t is t=10+1000d 2 , where d is the scraping thickness of the mixed slurry.
[0017] The drying method of the polyester plain weave fabric-based coated cloth with rice paper wetting effect provided by the present invention solves the problem of avoiding the decomposition of citric acid caused by overheating during the drying process, so that the combination of polyester and mixed slurry is more firm; at the same time, through the unidirectional control of hot air, the slurry can penetrate into the pores of the polyester under the action of wind during the drying process, so that a three-dimensional combination is formed between the polyester and the slurry; at the same time, the citric acid is fully retained, so that the formed coated cloth has hygroscopicity. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The figure is a schematic diagram of the process of the drying method according to the embodiment of the present invention.
[0019] In the figure: S1-heating and dehydrating polyester; S2-dipping citric acid treatment; S3-scrape coating slurry treatment; S4-Drying treatment of the coating surface; S5-Residual citric acid dehydration treatment.
[0020] Figure 2 This is a graph showing the droplet roundness evaluation results for polyester, rice paper, and polyester fabric-based coated cloth with solid contents of 0.5%, 1%, 1.5%, and 2%.
[0021] Figure 3 This is a graph showing the droplet area evaluation results for polyester, rice paper, and polyester fabric-based coated cloth with solid contents of 0.5%, 1%, 1.5%, and 2%.
[0022] Figure 4 It is a graph showing the droplet circumference evaluation results of polyester, rice paper, and polyester fabric-based coated cloth with solid contents of 0.5%, 1%, 1.5%, and 2%. DETAILED DESCRIPTION In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0024] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0026] The present invention provides a drying method for a polyester plain weave fabric-based coated cloth having a rice paper wetting effect, comprising: Step S1: heating and dehydrating polyester Obtain polyester fabric, heat and dehydrate the polyester, and then cool it down to between 30-40°C. The dehydrated polyester no longer contains moisture, and then keep the temperature of the polyester between 30-40°C (to keep the polyester with a certain tension and elasticity), so that when the polyester encounters the citric acid solution again, it has a greater adsorption capacity for the citric acid solution; Step S2: Dipping and citric acid treatment The polyester is immersed in a 3-5wt% citric acid solution. Since the polyester itself has a temperature of 30-40°C, it can absorb citric acid and water into the polyester after entering the citric acid solution. After the polyester comes out of the citric acid solution, the surface of the polyester, that is, the gaps, are all soaked with the citric acid solution. At this time, hot air with a temperature not exceeding 60°C is blown from bottom to top, so that the citric acid solution moves along the pores of the polyester to the upper surface to be concentrated in the pores and the upper surface of the polyester, and part of the water therein is evaporated while keeping the citric acid from being decomposed. The lower surface of the polyester is acted upon by the hot air, so that the citric acid solution on the polyester moves from bottom to top, and part of the water therein is blown away by the hot air in the form of steam, so that the concentration of the citric acid solution remaining on the polyester is increased, and the citric acid converges on the upper surface of the polyester. Since the upper surface of the polyester is used as a sizing surface, the citric acid on the upper surface will be more in contact with the mixed slurry, and then the hydroxyl groups in the citric acid solution will react with the carboxyl groups in the mixed slurry to produce an esterification reaction. Step S3: Scraping slurry treatment The polyester upper surface is coated with a mixed slurry whose main components are oxidized starch and carboxylated nanocellulose, and the hydroxyl functional group content of the oxidized starch in the mixed slurry is 1.05-1.1 times the carboxyl functional group content of the carboxylated nanocellulose, and the solid content of the oxidized starch and the carboxylated nanocellulose in the mixed slurry is 0.6-1wt%; the hydroxyl functional group content in the oxidized starch and the carboxyl functional group content in the carboxylated nanocellulose can be obtained by detection or experimental data and combined with theoretical analysis to calculate the weight ratio of the oxidized starch and the carboxylated nanocellulose, and then the oxidized starch, the carboxylated nanocellulose, the thickener, the preservative, the leveling agent, the dispersant, the defoaming agent, etc. are mixed and added in their respective orders; wherein the mixing step of the mixed slurry of the oxidized starch and the carboxylated nanocellulose comprises: The oxidized starch is made into gelatinized starch after adding water. The weight ratio of the oxidized starch to water can be adjusted as needed, for example, it can be prepared in a ratio of 1: (10-15), and then placed in a container at a high temperature of 90°C and stirred for 45 minutes; Prepare a carboxylated nanocellulose dispersion, wherein the carboxylated nanocellulose dispersion is mainly prepared by mixing carboxylated nanocellulose and water in a ratio of 1: (120-160); The gelatinized starch and the carboxylated nanocellulose dispersion are mixed and stirred evenly, and then a thickener, a preservative, a leveling agent, a dispersant, a defoaming agent, etc. are added. The proportions of these additives can be selected according to the weight percentage example 0.5%, 0.02%, 0.2%, 1.5%, 1.5% or other proportions for deployment.
[0027] The thickener includes one or more of an inorganic thickener (bentonite), a cellulose thickener (carboxymethyl cellulose), a polyacrylic thickener, and a polyurethane thickener (aqueous polyurethane thickener).
[0028] The preservative includes one or more of s-triazines or isothiazolinones.
[0029] Step S4: Drying the coated surface The coated surface is subjected to pressure drying treatment: hot air at 60-75℃ is blown evenly downward from the upper surface of the polyester to promote the mixed slurry to penetrate downward along the pores of the polyester, and the surplus hydroxyl groups of the oxidized starch in the mixed slurry are contacted and reacted with the citric acid on the upper surface and in the gaps of the polyester; the reason for setting the temperature range of 60-75℃ is to avoid the temperature exceeding 78℃, which may cause the citric acid to decompose and obtain anhydrate, so the drying treatment is carried out at a relatively low temperature (60-75℃) to ensure the drying effect; Step S5: Residual citric acid dehydration treatment After the citric acid and oxidized starch have fully reacted, hot air at 78-90°C is blown from bottom to top on the lower surface of the polyester to evaporate the residual moisture and decompose the unreacted citric acid hydrate to obtain anhydrate, while ensuring that the citric acid anhydrate will not continue to decompose into carbon dioxide and water; the anhydrate obtained in this way is hygroscopic.
[0030] The carboxylated nanocellulose has a diameter of 10-20 nm and a length of 0.5-1 μm, so the aspect ratio is between 25-100.
[0031] The thickness of the polyester is 0.5 mm, and the fabric density is 300-400 strands / 10 cm.
[0032] The oxidized starch and water were mixed, heated at 95°C, and mechanically stirred at 230 rpm for 45 min; then, the mixture was heated to 60°C for 15 min; At room temperature, the gelatinized oxidized starch solution and the cellulose nanofiber dispersion were mixed in a mass ratio of 2:8 and mixed evenly by magnetic stirring.
[0033] The scraping thickness d of the mixed slurry is 0.1-0.25 mm.
[0034] In the fourth step, the drying time t is t=10+1000d 2 , where d is the scraping thickness of the mixed slurry. That is to say, the drying time t is related to the scraping thickness of the mixed slurry, but it is not directly positively correlated, but is quadratically related to the thickness d of the wall chart. Therefore, the thicker the scraping thickness, the more accumulated drying time, which further makes the drying effect better.
[0035] Comparative Example 1 S1-heating and dehydrating the polyester, wherein the thickness of the polyester is 0.5 mm and the fabric density is 350 yarns / 10 cm, and after the dehydration treatment, the polyester is cooled to room temperature (35°C); S2-citric acid dipping treatment, the content of the citric acid solution is 3wt%, and the temperature of the hot air heated to the polyester after dipping in citric acid is 58°C; S3-slurry treatment with doctor blade coating, the solid content of oxidized starch and carboxylated nanocellulose in the mixed slurry was 0.5wt%; S4-Drying treatment of the coating surface, the hot air temperature used is 70℃; S5-residual citric acid dehydration treatment, the heating temperature is 80°C.
[0036] Comparative Example 2 S1-heating and dehydrating the polyester, wherein the thickness of the polyester is 0.5 mm and the fabric density is 350 yarns / 10 cm, and after the dehydration treatment, the polyester is cooled to room temperature (35°C); S2-citric acid dipping treatment, the content of the citric acid solution is 3wt%, and the temperature of the hot air heated to the polyester after dipping in citric acid is 58°C; S3-blade coating slurry treatment, the solid content of oxidized starch and carboxylated nanocellulose in the mixed slurry is 1wt%; S4-Drying treatment of the coating surface, the hot air temperature used is 70℃; S5-residual citric acid dehydration treatment, the heating temperature is 80°C.
[0037] Comparative Example 3 S1-heating and dehydrating the polyester, wherein the thickness of the polyester is 0.5 mm and the fabric density is 350 yarns / 10 cm, and after the dehydration treatment, the polyester is cooled to room temperature (35°C); S2-citric acid dipping treatment, the content of the citric acid solution is 3wt%, and the temperature of the hot air heated to the polyester after dipping in citric acid is 58°C; S3-blade coating slurry treatment, the solid content of oxidized starch and carboxylated nanocellulose in the mixed slurry was 1.5wt%; S4-Drying treatment of the coating surface, the hot air temperature used is 70℃; S5-residual citric acid dehydration treatment, the heating temperature is 80°C.
[0038] Comparative Example 4 S1-heating and dehydrating the polyester, wherein the thickness of the polyester is 0.5 mm and the fabric density is 350 yarns / 10 cm, and after the dehydration treatment, the polyester is cooled to room temperature (35°C); S2-citric acid dipping treatment, the content of the citric acid solution is 3wt%, and the temperature of the hot air heated to the polyester after dipping in citric acid is 58°C; S3-blade coating slurry treatment, the solid content of oxidized starch and carboxylated nanocellulose in the mixed slurry is 2wt%; S4-Drying treatment of the coating surface, the hot air temperature used is 70℃; S5-residual citric acid dehydration treatment, the heating temperature is 80°C.
[0039] In the above four comparative examples, only the solid contents of oxidized starch and carboxylated nanocellulose in the mixed slurry in step S3 are different (0.5%, 1%, 1.5%, 2%), and the other process parameters and links not listed are exactly the same, so as to obtain polyester fabric-based coated cloths obtained by drying slurries with different solid contents, and then the polyester fabric-based coated cloths obtained in the four comparative examples are tested with polyester and rice paper using the same test method to obtain the droplet roundness (reference Figure 2 )、Droplet spreading area (reference Figure 3 ), droplet circumference (reference Figure 4 ), it can be seen that when the solid content is 0.5% and 1%, the wettability effect of the coated cloth obtained after drying is closer to polyester and rice paper, and the wettability effect closest to rice paper is undoubtedly 1% solid content, and when the solid content exceeds 1%, the wettability effect of the polyester fabric-based coated cloth deviates significantly from that of rice paper. It can be seen that when the solid content exceeds 0.5%, the wettability effect begins to converge with that of rice paper, and when it exceeds 1%, it begins to deviate significantly, so it can be determined that when the mixed slurry with a solid content of 0.6-1% is treated by the drying method provided by the present invention, the wettability of the polyester fabric-based coated cloth obtained reaches a wettability effect closer to that of rice paper.
[0040] Based on this data support, the following embodiments are further provided: Example
[0041] S1-heating and dehydrating the polyester, wherein the thickness of the polyester is 0.5 mm and the fabric density is 350 yarns / 10 cm, and after the dehydration treatment, the polyester is cooled to room temperature (30°C); S2-citric acid dipping treatment, the content of the citric acid solution is 4wt%, and the temperature of the hot air heated to the polyester after dipping in citric acid is 60°C; S3-blade coating slurry treatment, the solid content of oxidized starch and carboxylated nanocellulose in the mixed slurry was 0.6wt%; S4-Drying treatment of the coating surface, the hot air temperature used is 75℃; S5-residual citric acid dehydration treatment, the heating temperature is 90°C. Example
[0042] S1-heating and dehydrating the polyester, wherein the thickness of the polyester is 0.5 mm and the fabric density is 300 yarns / 10 cm, and after the dehydration treatment, the polyester is cooled to room temperature (45°C); S2-citric acid dipping treatment, the content of the citric acid solution is 5wt%, and the temperature of the hot air heated to the polyester after dipping in citric acid is 55°C; S3-blade coating slurry treatment, the solid content of oxidized starch and carboxylated nanocellulose in the mixed slurry was 0.8wt%; S4-Drying treatment of the coating surface, the hot air temperature used is 60℃; S5-residual citric acid dehydration treatment, heating temperature is 78℃. Example
[0043] S1-heating and dehydrating the polyester, wherein the thickness of the polyester is 0.5 mm and the fabric density is 400 yarns / 10 cm, and after the dehydration treatment, the polyester is cooled to room temperature (40°C); S2-citric acid dipping treatment, the content of the citric acid solution is 4.5wt%, and the temperature of the hot air heated to the polyester after dipping in citric acid is 60°C; S3-blade coating slurry treatment, the solid content of oxidized starch and carboxylated nanocellulose in the mixed slurry was 0.9wt%; S4-Drying treatment of the coating surface, the hot air temperature used is 72℃; S5-residual citric acid dehydration treatment, the heating temperature is 85°C. Example
[0044] S1-heating and dehydrating the polyester, wherein the thickness of the polyester is 0.5 mm and the fabric density is 380 yarns / 10 cm, and after the dehydration treatment, the polyester is cooled to room temperature (38°C); S2-citric acid treatment, the content of the citric acid solution is 3wt%, and the temperature of the hot air for heating the polyester after the citric acid treatment is 53°C; S3-blade coating slurry treatment, the solid content of oxidized starch and carboxylated nanocellulose in the mixed slurry is 1wt%; S4-Drying treatment of the coating surface, the hot air temperature used is 65℃; S5-residual citric acid dehydration treatment, the heating temperature is 90°C.
[0045] Combination Figure 1According to the drying method provided by the present invention, in step S1, the passing polyester fabric is heated by the heat radiation effect formed by the electric heating wire, so that the moisture in the polyester fabric is positively emitted, and then the temperature of the polyester fabric is reduced to below 40° C. before entering the citric acid solution tank in step S2 by natural cooling or air cooling (if the ambient temperature is too high and the natural cooling rate is low, air cooling is used); In step S2, a step roller is provided in the citric acid solution tank, a cloth roller is provided at both ends of the outside, and a pair of clamping rollers are designed after leaving the citric acid solution tank to squeeze out the excess citric acid solution on the polyester cloth to make the citric acid solution on the polyester cloth uniform; then a hair dryer is used to blow hot air to the lower surface of the polyester cloth, and the temperature of the hot air does not exceed 60° C., so that the citric acid solution is blown to the upper surface, so that the citric acid concentration on the upper surface of the polyester cloth is higher, and the excess water is evaporated; In step S3, a material trough is used, and the scraping method can be a conventional scraping device. The specific scraping method can be a conventional method, which is not an innovation of the present invention. It is sufficient to ensure that the scraping thickness meets the requirements of the technical solution of the present invention. The scraping thickness designed by the present invention is about 0.5 mm. Step S4 is to use a hot air blower similar to that in step S2, but the temperature of the blown air is higher, between 60-75°C, and the direction of the blown air is from top to bottom toward the upper surface of the polyester fabric coated with the slurry, so that the slurry can penetrate downward along the pores of the polyester fabric; in this step, it is necessary to control a reasonable wind speed to avoid blowing away the slurry, and it is necessary to control the blower to blow air more evenly downward, so that the wind force exerted on the polyester fabric passing through the blower is basically the same at all locations; in order to make the wind force at all locations the same, a porous plate can be placed between the hair dryer and the upper surface of the polyester fabric, and a plurality of air holes evenly arranged on the porous plate can be provided, so that the air outlet speed of each air hole can be basically the same; Step S5 is similar to the hot air blower in step S2, and also blows from bottom to top. Its purpose is to decompose the remaining citric acid hydrate and separate the water molecules from the citric acid molecules, so that after the coating cloth is dried, the citric acid molecules combine with the water in the pigment during the painting process and can have better water absorption.
[0046] The drying method of the polyester plain weave fabric-based coated cloth with rice paper wetting effect provided by the present invention solves the problem of avoiding the decomposition of citric acid caused by overheating during the drying process, so that the combination of polyester and mixed slurry is more firm; at the same time, through the unidirectional control of hot air, the slurry can penetrate into the pores of the polyester under the action of wind during the drying process, so that a three-dimensional combination is formed between the polyester and the slurry; at the same time, the citric acid is fully retained, so that the formed coated cloth has hygroscopicity.
[0047] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0048] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for drying a polyester plain weave fabric-based coated cloth having a rice paper wetting effect, characterized in that: include: The first step is to heat and dehydrate the polyester, and then cool it down to between 30-40℃; The second step is to immerse the polyester in a 3-5wt% citric acid solution, and then blow hot air with a temperature not exceeding 60°C from bottom to top, so that the citric acid solution moves along the pores of the polyester to the upper surface to be concentrated in the pores and the upper surface of the polyester, and evaporate part of the water therein while keeping the citric acid from being decomposed; Step 3: Scrape the polyester upper surface with a mixed slurry whose main components are oxidized starch and carboxylated nanocellulose, and the hydroxyl functional group content of the oxidized starch in the mixed slurry is 1.05-1.1 times the carboxyl functional group content of the carboxylated nanocellulose; Step 4: Pressure drying the coated surface: Use hot air at 60-75℃ to blow downward from the upper surface of the polyester evenly, so as to make the mixed slurry penetrate downward along the pores of the polyester, and make the surplus hydroxyl groups of the oxidized starch in the mixed slurry contact and react with the citric acid on the upper surface of the polyester and in the gaps; Step 5: After the citric acid and oxidized starch have fully reacted, hot air at 78-90°C is blown from bottom to top on the lower surface of the polyester to evaporate the residual moisture and decompose the unreacted citric acid hydrate to obtain anhydrate, and ensure that the anhydrate of citric acid will not continue to decompose into carbon dioxide and water.
2. The method according to claim 1, characterized in that The carboxylated nanocellulose has a diameter of 10-20 nm and a length of 0.5-1 μm, so the aspect ratio is between 25-100.
3. The method according to claim 1, characterized in that The polyester is a polyester plain woven fabric, the thickness of the polyester is 0.5 mm, and the fabric density is 300-400 yarns / 10 cm.
4. The method according to claim 1, characterized in that The oxidized starch and water were mixed, heated at 95°C, and mechanically stirred at 230 rpm for 45 min, then kept at 60°C for 15 min; At room temperature, the gelatinized oxidized starch solution and the cellulose nanofiber dispersion were mixed in a mass ratio of 2:8 and mixed evenly by magnetic stirring; The scraping thickness d of the mixed slurry is 0.1-0.25 mm.
5. The method according to claim 1, characterized in that In the second step, the upper surface of the polyester is the starch-coated side and the lower surface is the non-starch-coated side.
6. The method according to claim 1, characterized in that In the third step, the mixing step of the mixed slurry of oxidized starch and carboxylated nanocellulose includes: Oxidized starch is made into gelatinized starch by adding water; preparing a carboxylated nanocellulose dispersion; The gelatinized starch and the carboxylated nanocellulose dispersion are mixed and stirred evenly.
7. The method according to claim 1, characterized in that In the third step, the mixed slurry also includes thickener, preservative, leveling agent, dispersant, defoaming agent, etc.
8. The method according to claim 1, characterized in that In the fourth step, the drying time t is t=10+1000d 2 , where d is the scraping thickness of the mixed slurry.
Citation Information
Patent Citations
Chinese art paper-like coating, Chinese art paper-like coating, preparation method and application of Chinese art paper-like coating
CN117738024A
Cited By
Coated fabric having wetting effect of xuan paper
WO2026180000A1